Artists, architects, and engineers: A further study of visual preferences scales - Welsh, George S.; Swartz, Jon D. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
Welsh Figure Preference Test (IVFPT) protocols from 84 outstanding individuals in their respective fields-28 artist, 30 architects, and 26 engineers-were scored for three scales that are of potential interest in personality assessment: Conformance (CF), Intellectence (IN), and Origence (OR). Significant differences were found among the three groups on three scales, differences that had been predicted on the basis o f a recently developed two-dimensional personality model and previous research with the WFPT. The findings for these three selected WFPT scales served to effectively differentiate these contrasting modes of visual experience, as exemplified by the three groups of outstanding individuals.